Simulasi Algoritma Monte Carlo dalam Memprediksi Pendapatan Penjualan Produk Kalsium Tiens Syariah - Zulfitri Yani; Sumijan (Jurnal Informatika Ekonomi Bisnis, 2021)
In meeting consumer needs, the availability of calcium products is a problem that needs attention. Items that are often sold will be the largest stock, so that the demand for finished goods is met and income will also increase. This study aims to predict the level of sales revenue for calcium products at stokies tiens 872, in determining which products will be provided for the following year. The data to be used is the sales data for calcium products from 2018 to 2019. Data processing is carried out using the Monte Carlo algorithm, then the data is processed and generated using random numbers taken randomly, after which it is converted or changed in the form of distribution with use simulation techniques to get the results. The results obtained in predicting the income level of sales of calcium products, by making comparisons with the sales data that were sold, namely Nutrient High Calcum Powder that existed in 2018, with simulation results in 2018 with a data accuracy rate of 91%, with the number of calcium products. as many as 1367 products. Then the data in 2019 with simulation results in 2019 with a data accuracy rate of 93% with the number of calcium products as many as 1667 products. With the resulting level of accuracy in the study, the monte carlo simulation can help the stockies predict sales revenue based on processed data, so that this study is able to predict the level of income for the following year.